Pengaruh Profitabilitas, Leverage, Modal Intelektual dan Reputasi Audit terhadap Nilai Perusahaan - Befi Widya Hermawan; Hermanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of profitability (ROA), leverage (DER), intellectual capital (VACA), and audit reputation on company value in the food and beverage sub-sector manufacturing industry consistently listed on the Indonesia Stock Exchange (IDX) during the reporting period from 2019 to 2023. Data obtained using purposive sampling techniques and processed through multiple linear regression analysis with the Stata statistical application concluded that there was no significant effect of profitability and leverage on Firm value, in contrast to intellectual capital which had a negative and significant effect. In contrast to audit reputation which has a significant positive effect on firm value.